An accurate UTD extension to a ray-launching algorithm for the analysis of complex indoor radio environments. Issue 1 (2nd January 2016) - Azpilicueta, Leyre; Aguirre, Erik; López-Iturri, Peio; Falcone, Francisco
Abstract : This paper deals with the efficient combination of two well-established electromagnetic methods, a shooting and bouncing Rays (SBR) algorithm on the basis of geometrical optics (GO) and diffraction calculation on the basis of the uniform theory of diffraction (UTD). While the conventional GO method is able to accurately calculate field contributions due to reflection and refraction, the further propagation of diffracted rays is generally not considered in SBR approaches. Thus, the aim of this work is to describe the implementation of diffracted rays according to the UTD concept into an SBR code. A convergence analysis to obtain the optimal calculation parameters for the diffracted rays is presented. This novel implementation with the optimal parameters allows modeling the radio wave propagation channel in complex indoor environments with a large number of obstacles. The comparison with real measurements proves that the proposed hybrid GO–UTD algorithm yields excellent results and that the UTD extension definitely improves the simulations of the ray-launching algorithm for realistic environments.